Exploring the Role of Public Policy in Adapting to the Challenges and Opportunities of Emerging Technologies - Yejide Adedeji (Journal of Public Representative and Society Provision, 2021)
This research paper investigates how government policy can be modified to meet the opportunities and threats posed by rapidly developing technologies. This article focuses on Examine how emerging technologies are affecting our democracy, personal lives, economy, and culture. New technology potential benefits and drawbacks are compared, and policy shortcomings and roadblocks are identified. The thesis also examines policy options for regulating emerging technologies like blockchain, cryptocurrencies, and the Internet of Things. The effectiveness and viability of various policy methods are reviewed, and the significance of public participation in technological policy-making is emphasized. The use of digital technologies, citizen juries, collaborative policy-making, education and awareness-raising campaigns, consultations, public hearings, and citizen juries are a few of the methods proposed to promote public participation and engagement in technological policy-making processes. The entire thesis emphasizes the value of proactive and transparent government with reference to technology improvements. Governments may better ensure that new technologies are used in ways that are beneficial for society, the economy, the environment, and everyone's rights and freedoms by allowing citizens to provide input on policy decision.